Integration of National Resources in the Context of Realizing Food Security - Nugroho, Arya Dewa; M. Syaiful Alim; Galih Rakasiwi Soekarno; Susilo Adi Purwantoro; Hikmat Zakky Al Mubaroq (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study highlights Indonesia's dependence on the food sector, especially rice. Despite diversification efforts, dependence on rice remains high. The availability of clean water and energy diversification are also crucial. In order to achieve sustainable food security, diversification of land and food commodities is needed, as well as wise management of water resources. This research uses a qualitative focused group discussion (FGD) method to explore the integration of national resources in an effort to realize food security in Indonesia. The results show that efforts to diversify food, manage clean water, and diversify energy sources are key in ensuring national food and energy security. The National Strategic Logistics Reserve Agency (BCLSN) has an important role in managing strategic food stocks and building a strong foundation for Indonesia's food security